Pathology of Heavy Metals Toxicity in Experimental Animal as Model Animals for Poisoning in Livestock - Riza Zainuddin Ahmad; Rida Tiffarent; Dianita Dwi Sugiartanti; Sutiastuti Wahyuwardani (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
Pollution is a global problem that can cause health problems in organisms. Heavy metal pollutants from the environment can enter the body systems of animals and humans through the food chain. Several cases of severe poisoning in animals have been reported, especially in grazing animals around landfills and show pathological findings. This article aims to describe the gross pathological and histopathological abnormalities of heavy metal poisoning Arsenic (As), Cadmium (Cd), Copper (Cu), Mercury (Hg), Manganese (Mn) and Lead (Pb) which are focused in laboratory animals and chickens as animal models of poisoning in livestock as animal consumption. In general, the organs that are heavily affected by heavy metals are the liver, kidneys, testes, and ovaries. This article is expected to increase the knowledge of readers and practitioners in the examination differential diagnosis for the possibility of heavy metal poisoning which can be acute or chronic.